PENGARUH PERLAKUAN ALKALI PADA LIMBAH KULIT KOPI DAN PENINGKATAN KECERNAANNYA DENGAN TEKNIK IN VITRO - A. Fariani., dkk (Jurnal Rekayasa Lingkungan)
This research was done to improve coffee pulp digestibility with alkali treatment and adding organic acid by in vitro. This research was done in two stage, fi rst stage was soaking in alkali fl uid and second stage was in vitro digestibility analysis, in Animal Feed and Nutrition Laboratory, Faculty of Agriculture, Sriwijaya University. Completely Randomized Design (CRD) used in 4 reatments and feed treatment was replicated 3 times. The treatments were: P0 (control), P1 (2 day soaking), P2 (3 day soaking) and P3 (4 day soaking). Observe parameters were tannin concentration, dry matter digestibility, organic matter digestibility, concentration of N-NH3 and (pH). The result showed that the treatment had nosignifi cant diference (P>0.01) on tannin concentration. However, it was signifi cantly difference on dry matter digestibility, organic matter digestibility, concentration of N-NH3, and (pH).Key Words: Coffee pulp, alkali treatment, digestibility, in vitro techniques